The Influence of Host Country’s Environmental Regulation on Enterprises’ Risk Preference of Multinational Investment - Peng, Cheng; Jiang, Hui (Frontiers in Environmental Science, 2021)
At present, China is in an important period of promoting high-quality economic development. In order to promote enterprises to “go global” and realize high-quality foreign investment, China advocates enterprises to abide by the environmental protection laws and regulations of the host country and standardize their environmental protection behaviors in foreign investment cooperation. However, the impact of the host country’s environmental regulation on Chinese enterprise’s multinational investment risk preference has not been paid enough attention. This paper makes an empirical analysis on how the host country’s environmental regulation affects the enterprises’ risk preference of multinational investment (MIRP) by using the samples of A-share listed companies in China from 2010 to 2018 and emphatically examines the moderating effects of enterprise’s green technology innovation and social responsibility on the relationship between host country’s environmental regulation and enterprises’ MIRP. It is found that, on the whole, the environmental regulation of the host country will significantly promote the enterprises’ MIRP. The green technology innovation will positively moderate the impact of the environmental regulation of host country on enterprises’ MIRP, while the engagement of corporate social responsibility will inhibit this positive impact.